2016
DOI: 10.3390/fi8020009
|View full text |Cite
|
Sign up to set email alerts
|

User Perception of Facebook App Data Access: A Comparison of Methods and Privacy Concerns

Abstract: Users share vast amounts of personal information online, but are they fully aware of what information they are sharing and with whom? In this paper, we focused on Facebook apps and set out to understand how concerned users are about privacy and how well-informed they are about what personal data apps can access. We found that initially, subjects were generally under-informed about what data apps could access from their profiles. After viewing additional information about these permissions, subjects' concern ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 12 publications
3
28
0
1
Order By: Relevance
“…Notification tools can be very useful to enhance privacy awareness for unconsented data collection. Note that Golbeck et al have shown that the privacy awareness of users can be changed significantly through educational methods [11]. When participants were asked which action they would want to take if notified that friends' apps are about to collect their information (multiple answers allowed), 99 out of 114 participants answered that they would restrict access to their personal data while 8 participants answered that they would unfriend their Facebook friend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notification tools can be very useful to enhance privacy awareness for unconsented data collection. Note that Golbeck et al have shown that the privacy awareness of users can be changed significantly through educational methods [11]. When participants were asked which action they would want to take if notified that friends' apps are about to collect their information (multiple answers allowed), 99 out of 114 participants answered that they would restrict access to their personal data while 8 participants answered that they would unfriend their Facebook friend.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 81 % of users are at least very concerned about collateral information collection through apps of their friends without their approval. Note that Golbeck et al [11] have investigated how informed users are regarding the privacy risks of using Facebook apps. Their findings show that users do not always comprehend what type of data is collected by apps even when they have installed the app themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Golbeck and Mauriello [9] have shown that the average Facebook users significantly underestimate the amount of data they that they give access to third party applications. Moreover, they also noted that most of us tend to overlook the privacy [8] terms and policies on the Web.…”
Section: Privacy In Action: Looking Backmentioning
confidence: 99%
“…Recently, with the emergence of social media and mobile apps, consent acquiring mechanisms have changed. Researchers [9] have found that the current methods of asking user consent in social media platforms, such as Facebook are ineffective and most of the users underestimate the authorization given to the third party applications. In some cases, developers may not provide accurate information to the users for the consenting decision.…”
Section: User Consent Acquisitionmentioning
confidence: 99%
“…Recently, with the emergence of social media and mobile apps, consent acquiring mechanisms have changed. Researchers [19] have found that the current methods of asking user consent in social media platforms, such as Facebook are ineffective and most of the users underestimate the authorization given to third party applications. In some cases, developers may not provide accurate information to users for the consent decision.…”
Section: Consent Acquisition and Negotiationmentioning
confidence: 99%